TANGGUNG JAWAB NOTARIS DALAM HAL TERJADI PELANGGARAN PEMBUATAN AKTA OTENTIK DI KOTA SAMARINDA - Yuni, Dyna Dwi Fransisca (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
AbstractDyna Dwi Fransisca Yuni, 2019 : The purpose of this research is to analyze about the responsibilities of a Notary in Samarinda City against the authentic deed made by a Notary and to know about the sanctions if the Notary made a violation law that caused a deed lose its perfect verifying force value or the degradation of its evidentiary power commonly called an authentic deed with a legal disability.This study uses an empirical juridical research methods, using the rules in Law Number 2 of 2014 Concerning Amendment to Law Number 30 of 2004 Regarding Notary Position and reseaarch conducted by collecting data and information directly in Notary’s office.The responsibility of a Notary as a Public Official include the responsibility of the Notary itself relating to the deed. The forms of responsibilities of a Notary are: the notarial responsibility of a Notary publicly, a criminal Notary’s responsibility, a notarial responsibility based on a Notary regulation and a notarial responsibility under the Notary Code of Ethics.